Insulin resistance is related to cognitive decline but not change in CSF biomarkers of Alzheimer's disease in non‐demented adults. Issue 1 (28th July 2021) - Ennis, Gilda E.; Koscik, Rebecca L.; Ma, Yue; Jonaitis, Erin M.; Van Hulle, Carol A.; Betthauser, Tobey J.; Randall, Allison M.; Chin, Nathaniel; Engelman, Corinne D.; Anderson, Rozalyn; Suridjan, Ivonne; Kollmorgen, Gwendlyn; et al.
Abstract: Introduction: We investigated whether insulin resistance (IR) was associated with longitudinal age‐related change in cognition and biomarkers of Alzheimer's disease (AD) pathology and neurodegeneration in middle‐aged and older adults who were non‐demented at baseline. Methods: IR was measured with homeostatic model assessment of insulin resistance (HOMA2‐IR). Core AD‐related cerebrospinal fluid (CSF) biomarkers and cognition were assessed, respectively, on n = 212 (1 to 5 visits) and n = 1299 (1 to 6 visits). Linear mixed models tested whether HOMA2‐IR moderated age‐related change in CSF biomarkers and cognition. Linear regressions tested whether HOMA2‐IR x apolipoprotein E ε4 allele ( APOE ε4) carrier status predicted amyloid beta [Aβ] chronicity (estimated duration of amyloid positron emission tomography [PET] positivity) (n = 253). Results: Higher HOMA2‐IR was associated with greater cognitive decline but not with changes in CSF biomarkers. HOMA2‐IR x APOE4 was not related to Aβ chronicity but was significantly associated with CSF phosphorylated tau (P‐tau)181 /Aβ42 level. Discussion: In non‐demented adults IR may not be directly associated with age‐related change in AD biomarkers. Additional research is needed to determine mechanisms linking IR to cognitive decline.